2008
DOI: 10.1007/s11214-008-9330-7
|View full text |Cite
|
Sign up to set email alerts
|

The STEREO IMPACT Suprathermal Electron (STE) Instrument

Abstract: The Suprathermal Electron (STE) instrument, part of the IMPACT investigation on both spacecraft of NASA's STEREO mission, is designed to measure electrons from ∼2 to ∼100 keV. This is the primary energy range for impulsive electron/ 3 He-rich energetic particle events that are the most frequently occurring transient particle emissions from the Sun, for the electrons that generate solar type III radio emission, for the shock accelerated electrons that produce type II radio emission, and for the superhalo electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Further information about the electron behavior across the ICME is provided by SWEA and the suprathermal electron instrument (STE; Lin et al 2008) on board STEREO, as shown in Figure 6. The electron energies range from $1 eV to 100 keV.…”
Section: Sep Eventsmentioning
confidence: 99%
“…Further information about the electron behavior across the ICME is provided by SWEA and the suprathermal electron instrument (STE; Lin et al 2008) on board STEREO, as shown in Figure 6. The electron energies range from $1 eV to 100 keV.…”
Section: Sep Eventsmentioning
confidence: 99%
“…Using high sensitivity measurements from the SupraThermal Electron instrument (Lin et al 2008) on the STEREO, Wang et al (2012) reported that the power-law spectral index δ of superhalo electrons observed during quiet-times near solar minimum ranges from ∼ 1.5 to ∼ 3.4, with an average of ∼ 2.35 ± 0.45. The observed density of superhalo electrons, about 10 −9 −10 −6 of the solar wind proton density, decreases with the decay of solar cycle, while δ has no solar-cycle variation.…”
mentioning
confidence: 99%
“…To measure the kinetic energy of the particles, each sensor head contains a solid state detector (SSD) with an ultra-thin window and several pixels, which is based on technology used for STE on STEREO (Lin et al 2008) (see Sect. 4.1).…”
Section: The Suprathermal Electron Proton (Step) Sensormentioning
confidence: 99%